MARKET RETURN, VOLATILITY AND TRADING VOLUME DYNAMICS AFTER ECONOMIC CRISIS - Bramantyo Djohanputro (Faculty of Economics and Business, Universitas Gadjah Mada, 2011)
This paper attempts to explore the relationships of return – trading volume and volatility – trading volume. Trading volume may represent a proxy of information, liquidity, andmomentum. The up and down of trading volume, therefore, contain certain information that can be extracted by traders to make investment decision. Regressions of market returnon its lags, volume, and conditional variance and regressions of volatility on its lags, volume, and conditional variance are employed. Traders may respond positive informationdifferently from negative information. To accommodate such behaviour, threshold autoregressive conditional heteroskedasticity or TARCH is employed. Using market data of Indonesia Stock Exchange between economic crisis and before sub-prime mortgage crisis (from year 2000 to 2007) indicate the existence of return – volume relationships as well as volatility – return relationships albeit not very strong. There is also an indication that traders respond positive information differently from negative information concerningreturn movements but there is no indication concerning volatility movements.Keywords: return, volatility, volume, TARCH